Increased Virulence of Culicoides Midge Cell-Derived Bluetongue Virus in IFNAR Mice - Barbara S. Drolet; Lindsey Reister-Hendricks; Christie Mayo; Case Rodgers; David C. Molik; David Scott McVey (Viruses)
Bluetongue (BT) is a Culicoides midge-borne hemorrhagic disease affecting cervids and ruminant livestock species, resulting in significant economic losses from animal production and trade restrictions. Experimental animal infections using the α/β interferon receptor knockout IFNAR mouse model and susceptible target species are critical for understanding viral pathogenesis, virulence, and evaluating vaccines. However, conducting experimental vector-borne transmission studies with the vector itself are logistically difficult and experimentally problematic. Therefore, experimental infections are induced by hypodermic injection with virus typically derived from baby hamster kidney (BHK) cells. Unfortunately, for many U.S. BTV serotypes, it is difficult to replicate the severity of the disease seen in natural, midge-transmitted infections by injecting BHK-derived virus into target host animals. Using the IFNAR BTV murine model, we compared the virulence of traditional BHK cell-derived BTV-17 with C. sonorensis midge (W8) cell-derived BTV-17 to determine whether using cells of the transmission vector would provide an in vitro virulence aspect of vector-transmitted virus. At both low and high doses, mice inoculated with W8-BTV-17 had an earlier onset of viremia, earlier onset and peak of clinical signs, and significantly higher mortality compared to mice inoculated with BHK-BTV-17. Our results suggest using a Culicoides W8 cell-derived inoculum may provide an in vitro vector-enhanced infection to more closely represent disease levels seen in natural midge-transmitted infections while avoiding the logistical and experimental complexity of working with live midges.